2019
DOI: 10.33828/sei.v30.i4.10
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Affecting the Teaching and Learning of Integrated Science in Rural Junior High Schools in Ghana

Abstract: The study investigated challenges affecting the teaching and learning of Integrated Science in rural Junior High Schools (JHSs) in the Effutu Municipality in the central region of Ghana. A qualitative approach was employed. Purposive sampling was employed to select six rural JHSs from the municipality. A closed-structured interview was used to collect data from head teachers, teachers, and pupils, and then analyzed. The study revealed that inadequate instructional materials and poor proficiency of pupils in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The role of an educator is to empower learners with knowledge using language as a medium of instruction. The preferred language of teaching and learning across the curriculum in English, and it takes time to develop this language in rural schools (Quansah, Sakyi-Hagan & Essiam, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of an educator is to empower learners with knowledge using language as a medium of instruction. The preferred language of teaching and learning across the curriculum in English, and it takes time to develop this language in rural schools (Quansah, Sakyi-Hagan & Essiam, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the unfortunate fact is that both FET novices The participants recognized the importance of effective information comprehension during the teaching of all subjects across the curriculum. The lack of this crucial competence jeopardizes inexperienced teachers' ability to deliver successful lessons (Evans & Nthulana, 2018;Quansah, Sakyi-Hagan & Essiam, 2019). Jordaan, Welman, and Stephen (2004) make the case that weak comprehension of any subject matter hinders second-language speakers, a claim that is borne out when inexperienced teachers begin asking serious questions to test learners' level of understanding before the lesson is facilitated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently critical issues in science education all over the world, prompting many researchers to contribute to this discourse. These issues are divided into five categories: teacher factors, student factors, curriculum factors, school factors, societal factors, and national/policy factors (Adu-Gyamfi, 2014;Parker et al, 2018;Quansah et al, 2019). According to Parker et al (2018), one of the main contributors to such challenges in Ghana is teachers' inadequate subject knowledge background which affects how the teacher develops pedagogical content knowledge, in addition to self-confidence and attitudes while instructing topics on Integrated Science.…”
Section: Introductionmentioning
confidence: 99%
“…The above challenges were identified to influence teachers' selection of appropriate teaching methods, students' performance and interest in science and students' participation in science lessons. Quansah et al (2019) identified similar challenges and proposed that Integrated Science teachers should be trained to improve instructional materials by using readily available materials in the environment to teach the course. It is important to recognize that using improvised materials to teach effectively can address methodological issues.…”
Section: Introductionmentioning
confidence: 99%